Powtórzenie (recydywa) przestępstw w rosyjskim prawie karnym XIX w. - Machlańska, Joanna (Czasopismo Prawno-Historyczne, 2018)
The legal institution of the recurrence of crime is nothing new in Russian criminal law. Recidivism, in the colloquial meaning of the term, is considered to be a repetition of the offence. Furthermore, it is treated as such regardless of whether the new forbidden act is the same, similar or different from the previous one. It is also classified as recidivism regardless of the period of time which elapsed from the previous criminal act. The following article presents the construction of the recurrence of crime in the Russian legislation in the 19th century (at the time the legislator did not use the term “recidivism”). Furthermore, an analysis of various regulations from that period is included, i.e., the Digest of Laws of the Russian Empire, the Code of Criminal and Correctional Punishments as well as the statute concerning punishments imposed by the justices of the peace.